Remoção de bezerros e/ou ECG na taxa de prenhez de vacas Nelore paridas submetidas à IATF e seus eleitos no desempenho das crias - Carvalho, Everton Rodolfo de [UNESP] (2014)
The experiment aimed to evaluate pregnancy rate of Nelore cows calved synchronized with TAI protocol and subjected to three different treatments: calf removal (CR), application of equine chorionic gonadotropin (eCG) and the association of CR and eCG (CR+eCG). Animals were used in 2643, including 599 primiparous and multiparous 2044 in two consecutive breeding seasons (BS), and all the animals were synchronized with the same TAI protocol based P4 and E2. The first year the cows were served with 91.9±16.5 days postpartum medium, and the second year with 51.4±8.38 days. The mean pregnancy rate of cows was 56.1 % and differed between BS (P<0.01) in the second year was higher (60.1%) than in the first (52.2%), but no interaction between year and treatment (P=0.30). Multiparous cows tended (P = 0.08) to have a higher pregnancy rate (56.9%) than primiparous (53.0%). There was a tendency interaction in pregnancy rate between order and treatments (P=0.06), multiparous pregnancy rate was higher for CR (60.7%) and eCG (56.3%) than for CR+eCG (53.9 %), and primiparous was not different. In multiparous with body score condition (BCS) <2.75 pregnancy rate among treatments (55.2%, 54.4 % and 45.1 %) was similar to CR and eCG, and both greater CR+eCG, respectively. As for BCS ≥2.75 the pregnancy rate between treatments was not different. In primiparous no interaction between BCS and treatments (P=0.13). In the second year were detected estrous behavior and cyclicity at beginning of protocol. The rate of heat detection was different between treatments (P<0.01), whereas cows treated with CR (70.2%) and CR+eCG (68.1%) had higher expression of estrus than eCG (55.2%). Cows with presence of CL treated with CR (67.5%) and CR+eCG (70.6 %) were higher pregnancy rate than eCG (50.0%), and cows without CL was not different. The cows was divided in two weaning weight classes (210 days), higher our less that median (>Median our <Median). In the first year not ...